Coconut Fiber Panel Towards Acoustical Performance - Yaakob, Mohd Yuhazri; Balkrishnan, Paramananthan; Husin, Mohd Amirhafizan; Sihombing, Haeryip (International Journals of Engineering and Sciences Publisher, 2019)
In this research, the natural material fiber was intended to replace the synthetic fiber to reduce its dependency on synthetic materials. Basically, the use of natural material can minimize the cost in terms of materials and processing as well as to conserve the environment by reducing the waste of natural material. An experimental investigation was conducted to explore the sound absorption properties of coconut fiber with and without holes reinforced polyurethane (PU) for acoustic applications. The materials used in this study were coconut fiber as a reinforcement and PU as a matrix. The absorption coefficient of the acoustic panel was measured by using impedance tube and reverberation room testing. The results reveal that S3 shows good agreement in absorption coefficient value which is 0.75 between the frequencies of 3500 to 4000 Hz. The findings of this study also suggest that the absorption coefficient of CSM coconut fiber filled with PU without holes shows better perfomance compared to CSM coconut fiber filled with PU with holes 3 mm or 6 mm. Implications of the results and future research directions are also presented.